Canonical Correlation Analysis of Student Perception on Instructional Quality and Satisfaction - Encabo, Henry C. (JPAIR Multidisciplinary Research, 2011)
The study models student perceptions on instructional quality and student satisfaction using canonical correlation analysis. Data from two survey occasions were modeled to assess the strength and relative consistency of the instructional quality variables in predicting student satisfaction. Results show that student’s perception on the adequacy, usefulness, accessibility, safety and convenience of the learning facilities and their perception on the faculty teaching strategies and subject matter knowledge are the most influential factors of student satisfaction. Canonical functions and cross-loadings derived from the data sets show similar pattern or trend which is taken to indicate consistency of the models. The implication of the findings to managing student satisfaction among higher education institutions is briefly discussed.